Cognitive effects of hormone therapy in men with prostate cancer - Christian J. Nelson; Jennifer Lee; María Cecilia Gamboa; Andrew Roth (2008)
Abstract BACKGROUND. Men who receive androgen‐deprivation therapy (ADT) for prostate cancer experience several side effects from this treatment. A few recent studies have examined the cognitive implications of ADT and how they impact a patient's treatment decision‐making, occupational pursuits, and quality of life. For this report, the authors explored possible mechanisms for this association, reviewed research in animal studies and aging men, and examined the growing literature focused on the relation between ADT and cognitive functioning in patients with prostate cancer. METHODS. A systematic literature search was conducted using the PubMed and Information Sciences Institute Web of Knowledge‐Web of Science databases to identify relevant studies that investigated the relation between ADT in men with prostate cancer and its cognitive effects. RESULTS. Testosterone and its derivatives may have an impact on cognition through several mechanisms in the brain, as supported by studies of animals and in aging men. Studies that researched the impact of ADT on cognition in patients with prostate cancer patients were designed relatively well but suffered from small sample sizes. Between 47% and 69% of men on ADT declined in at least 1 cognitive area, most commonly in visuospatial abilities and executive functioning. Some studies reported contradictory results with increased functioning in verbal memory. CONCLUSIONS. There is a strong argument that androgen‐ablation therapy is linked to subtle but significant cognitive declines in men with prostate cancer. The authors believe that clinicians should become aware of this correlation as the use of ADT increases and should inform and monitor patients for this possible side effect of treatment. Cancer 2008. ©2008 American Cancer Society.